Contrastive Analysis of Indonesian and English Phonological Systems: Implications for Pronunciation Teaching - Kamsinah Kamsinah; Nurasia Natsir (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This contrastive linguistic study examines the phonological systems of Indonesian and English to identify areas of difficulty for Indonesian learners of English pronunciation. Through a systematic comparison of vowel and consonant inventories, phonotactic constraints, stress patterns, and prosodic features, this research identifies key points of interference that contribute to pronunciation challenges. The study employs acoustic analysis of speech samples from 120 Indonesian learners of English across different proficiency levels, combined with perceptual assessments by native English speakers. Findings reveal significant differences in vowel systems, consonant clusters, word stress placement, and intonation patterns that directly correlate with pronunciation difficulties. The research proposes a pedagogical framework that integrates principles of contrastive analysis with contemporary pronunciation teaching methodologies, including explicit phonological instruction, acoustic modelling, and technology-enhanced practice. The implications suggest that pronunciation instruction can be significantly improved through targeted interventions that address language-specific interference patterns while building on positive transfer opportunities.